PENTINGNYA PEMAHAMAN YANG AKURAT TENTANG ADHD UNTUK MASYARAKAT DAN PENDIDIK - Prifiantari, Siska; Mulyana, Edi Hendri; Qonita, Qonita (JPI (Jurnal Pendidikan Inklusi), 2023)
This study uses a literature study method with a descriptive qualitative approach to provide deep insight into the phenomenon of ADHD, identify needs that must be met, and formulate concrete steps to improve understanding and support for children with ADHD and their families. The results showed that there is stigma and incomprehension in society related to ADHD, influenced by lack of in-depth understanding, mental health literacy in the education curriculum and media stereotypes. ADHD plays an important role in society and education, but there are challenges in understanding and support. Intensive education efforts, outreach campaigns, mental health literacy integration, and inclusion strategies are expected to reduce stigma, increase understanding, and create a more supportive environment for children with ADHD.